ANALISIS KEBUTUHAN AIR BERSIH KECAMATAN KOTA BESI KABUPATEN KOTAWARINGIN TIMUR ( Clean Water Needs Analysis Besi City District, Kotawringin Timur Regency) - Miming Virganinda Virganinda; Jahriansyah , (Huma Tabalien Jurnal (HTJ) Teknik Sipil, 2022)
Kota Besi Subdistrict is a District with moderate population growth, where the demand for clean water is also growing and also increasing. And most of the residents in the sub-district use river water directly or use wells for their daily needs because most of these areas have not been served by PDAM clean water because the distance between villages is very far. The purpose of writing this research is to find out the magnitude of the demand for clean water in Kota Besi Subdistrict in the next 10 years and also to determine the capacity of the reservoir to meet the demand for clean water in the next 10 years. In this study, the calculation of population projections for the last 10 years and the projected addition of PDAM subscribers for the last 10 years are analyzed using 3 methods, namely the arithmetic method, the geometric method and also the linear regression method. The data used in this study are population data for the last 5 years and also data on the number of PDAM customers for the last 5 years. The method used in this study is descriptive quantitative analysis of water needs. The results of this study obtained a prediction of the population in the next 10 years, namely 26,155 people. Meanwhile, the number of subscribers is around 888 people with a total connection of 895 connections. Keywords: clean water needs, population, PDAM, number of customers, reservoirs